Legal and moral aspects of transplantation - Głowala, Sylwia Magdalena (Journal of Education, Health and Sport, 2018)
January 26, 1966 r. In the Department of Surgery, Medical University of Warsaw, a team of doctors in Poland made the first successful kidney transplant. It was the beginning of a difficult path Polish transplantation.The increase in demand for services of transplantation medicine, the dynamic development of this field and the lack of alternative treatments for end-stage organ failure makes transplants are still hotly debated.The author discusses the legal regulations in Poland transplantation, ethical issues and presents the possibility of transplantation medicine and its importance in the light of the teachings of the Church. From the outset, the sine qua non of organ transplantation was a statement the death of a potential donor. This requirement, referred to in the literature dead donor rule (called. Dead donor rule, DDR) is a legal and ethical justification for thousands of transplants. However, according to some authors, this rule has a greater potential to undermine confidence in transplants than to promote them. In their opinion, better solution to protect the transplant the alleged abuse would be to obtain informed consent from patients or their families for organ donation and therefore to stop life-sustaining treatment in situations of irreversible neurological injuries.This position is confirmed by studies that suggest that reliable information related to the degree of neurological damage potential donor consent and respect for his family or for society are more important than concerns about its vital status. The aim of this paper is to discuss the issue of transplants in the dimension of legislative and legal and ethical.